A Formulation Study for Enteric Microspheres of Tenoxicam Using Cellulose Acetate Phthalate Part-I: DTA/TG Analysis - OZLEN SAHIN, NEFISE; ARSLAN, HAKAN (Asian Journal of Chemistry, 2010)
Tenoxicam is an antiinflammatory drug causing irritation on stomach mucosa upon per oral administration in the form of tablets or hard gelatin capsules. Preparation of cellulose acetate phthalate microspheres of tenoxicam with solvent evaporation technique was suggested to overcome gastric irritancy of the pure drug. At first, it was determine to conduct preformulation studies. Thermal behaviour of pure drug (tenoxicam), polymer (cellulose acetate phthalate) and their physical mixtures was investigated as part of preformulation studies. Differential thermal analysis and thermogravimetry techniques were used for this purpose. The thermal analysis data obtained in this study revealed that there is no interaction between the polymer and the pure drug, indicating the appropriateness of the polymer of choice for preparation of enteric micropsheres.